2007
DOI: 10.1016/j.ejcts.2006.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve-sparing repair with autologous pericardial leaflet extension has a greater early re-operation rate in congenital versus acquired valve disease☆

Abstract: There was no significant difference in early or late mortality and late reoperation rate between the two groups. Early reoperation rate was higher in the congenital versus the acquired aortic valvular disease group. This study supports the fact that the valve-sparing technique is safe and reproducible and repeatable in patients with acquired valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Major concerns are related to possible patch dehiscence, calcification, degeneration, thickening and retraction. Several authors have reported on the use of several materials for cardiac reconstruction [1][2][3][4], with various short-and long-term results. The ideal patch should be a bioscaffold, which would be pliable, haemostatic and resistant to tearing; should not shrink or calcify; should not induce an inflammation cascade and should grow with the patient and promote regeneration of native tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Major concerns are related to possible patch dehiscence, calcification, degeneration, thickening and retraction. Several authors have reported on the use of several materials for cardiac reconstruction [1][2][3][4], with various short-and long-term results. The ideal patch should be a bioscaffold, which would be pliable, haemostatic and resistant to tearing; should not shrink or calcify; should not induce an inflammation cascade and should grow with the patient and promote regeneration of native tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we currently avoid using the SIS-ECM scaffold for reconstruction of small PAs in infants. Different techniques of semilunar valve repair have been proposed in the current literature so as to preserve the native valve, such as the leaflet extension technique with pericardium [1,10], which has provided generally good early results in the acquired and congenitally affected AoV. It is well known that the limiting factor of the longterm function of extended aortic leaflets is the durability of the material used for extensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that killing of pericardial cells with ethanol or glutaraldehyde fixation does prevent the accelerated degeneration of living pericardium [15] and is essential if a pericardial leaflet structure is expected to be long-lasting. Although the immunologic response and its effect on long-term durability is not completely understood [16,17], it becomes increasingly clear that autologous pericardium, treated with glutaraldehyde has a good longterm durability in aortic position [18][19][20]. Al Halees et al [14] published the largest series of autologous pericardial aortic valve prosthesis in 65 patients with a mean age of 30 years and the longest follow-up of 16 years.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, untreated fresh autologous pericardium might possess true growth, but distensibility as well. Despite good short-and mid-term results, it is associated with a high degeneration rate in the long term (11)(12)(13)(14) and is associated with bacterial endocarditis (8,10,15). Bovine pericardium-used as leaflet extension-has been shown to be less effective as compared to autologous pericardium (16,17), and autologous pericardium has greater resistance to retraction.…”
Section: Currently Used Patch Materials For Valve Repairmentioning
confidence: 99%